Gain of chromosome 3q is an early and consistent genetic aberration in carcinomas of the vulva. Issue 1 (1st January 2005) - Stoltzfus, P.; Heselmeyer-Haddad, K.; Castro, J.; White, N.; Silfverswärd, C.; Sjövall, K.; Einhorn, N.; Tryggvason, K.; Auer, G.; Ried, T.; Nordström, B.
Abstract : The aim was to determine whether specific gains of chromosome 3q and laminin-5γ2-chain expression can improve early detection of invasive capacity in precancerous and squamous cell carcinoma of the vulva (VSCC). Six VSCC and three precancerous lesions were studied. Multicolor fluorescence in situ hybridization (FISH) probe sets were applied to nuclei suspensions prepared from archival material using the Hedley method. The probe panel consists of the centromers of chromosome 7, chromosome 3, and the TERC gene residing on the long arm of chromosome 3. Laminin-5γ2-chain immunohistochemical analysis was performed on corresponding specimens and was expressed only in the VSCC. The genome-specific FISH analysis revealed 3q amplification in 43% of the nuclei analyzed for the VSCC and 22% of the nuclei for the precancerous lesions. Low-level 3q amplifications were found in precancerous lesions with an average fold increase of 1.15 for 3q. The invasive lesions showed higher average fold increases for 3q, averaging 1.32. Laminin-5γ2-chain protein was expressed only in VSCC, whereas 3q gains were observed both in precancerous lesions and in VSCC, indicating that gain of chromosome 3q is an early and consistent event during carcinogenesis of VSCC.